An iris puncture technique for restoration of the anterior chamber in vitrectomy for pediatric vitreoretinopathies - Chen, Chunli; Hu, Feng; Tian, Tian; Cheng, Yizhe; Fei, Ping; Zhao, Peiquan (Frontiers in Pediatrics, 2022)
Purpose To present a novel usage of iris puncture-assisted lensectomy with anterior vitrectomy or vitrectomy in pediatric patients with the absence of anterior chamber caused by various advanced vitreoretinopathies complicated with capsule-endothelial, iris-endothelial adhesion, and secondary glaucoma. Design Prospective study. Materials and methods Forty-one patients were enrolled in this consecutive, prospective study. The iris puncture was performed in all patients using a 20G Vitrectomy Microsurgical Knife, followed by the lensectomy with anterior vitrectomy or vitrectomy. Demographic information, the number of iris puncture times, surgical procedure, intraoperative and postoperative complications, therapy, and prognosis were collected. Patients were followed up for at least 6 months. Results A total of 18 female patients and 23 male patients were included, with a mean age of 9.5 ± 7.5 months. The formation of anterior chamber formation was achieved in 28 (68.3%) eyes, with only 1 initial episode of iris puncture, 11 (26.8%) patients required 2 episodes, and 3 episodes of iris puncture, with additional external drainage of subretinal fluid, were needed in the remaining 2 (4.9%) patients. Except for iris incarceration, which occurred in 7 (17%) eyes during operation, there was no iridodialysis or subretinal fluid overflow during operation. At the last visit (mean: 12.16 ± 5.38 months of follow-up), all eyes had a reconstructed anterior chamber with normal depth. No synechiae between the iris and the cornea occurred after surgery. The mean postoperative intraocular pressure was 6.23 ± 1.64 mmHg. A hazy cornea vanished in 31 out of 41 (75.6%) eyes, relieved in 8 out of 41 eyes (19.5%), and 2 out of 41 eyes (4.88%) did not change. In the 25 eyes accepting vitrectomy and lensectomy, 20 out of 25 (80%) achieved different degrees of reattachment. Conclusion The innovative iris puncture technique is effective, simple, and safe management for the anterior chamber disappearance caused by various advanced pediatric vitreoretinopathies, which helped to lower the intraocular pressure and offers a chance for lensectomy with anterior vitrectomy or vitrectomy.